2019
DOI: 10.1111/jop.12967
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of transforming growth factor beta receptor 1 polymorphisms in patients with oral cancer

Abstract: Objective: To investigate possible associations between disease-specific survival (DSS) of oral cancer and single nucleotide polymorphisms (SNPs) in transforming growth factor beta receptor 1 (TGFBR1). Methods:Using iPLEX Sequenom MassARRAY platform, three SNPs in TGFBR1 gene were genotyped in 356 newly diagnosed patients with histologically confirmed primary oral cancer. Demographic and clinical information of all cases were obtained from face-to-face interviews and electronic medical records, and telephone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Knobloch et al [ 31 ] identified a significant association between TGF-βR1 rs334348 and both the occurrence and advancement of HNSCC. Chen et al [ 32 ] discovered that the TGF-βR1 rs334348 polymorphism may modulate the progression of oral cancer by regulating the expression of TGF-βR1 and diminishing its ability to phosphorylate Smad-2 and Smad-3. Moreover, the researchers detected a synergistic association between TGF-βR1 rs334348 GA or GG genotype and the improved DSS of patients treated with radiotherapy, implying the potential clinical relevance of this genetic alteration in cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…Knobloch et al [ 31 ] identified a significant association between TGF-βR1 rs334348 and both the occurrence and advancement of HNSCC. Chen et al [ 32 ] discovered that the TGF-βR1 rs334348 polymorphism may modulate the progression of oral cancer by regulating the expression of TGF-βR1 and diminishing its ability to phosphorylate Smad-2 and Smad-3. Moreover, the researchers detected a synergistic association between TGF-βR1 rs334348 GA or GG genotype and the improved DSS of patients treated with radiotherapy, implying the potential clinical relevance of this genetic alteration in cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] It may act as a tumor suppressor gene during tumor development and progression. [ 31 ] It is a highly specific in vivo inhibitor of TGF-β as decorin and biglycan bind to and inhibit TGF-β activity. [ 32 ] It sequesters and reduces the stromal bioavailability of TGF-β, which is therefore incapable of initiating downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…FADS1 rs174549 is determined to be a potentially independent and favorable factor in predicting oral cancer PFS HR-0.52 (95% CI: 0.29-0.93) for patients with CCRT (Table 1) [34]. TGFBR1 plays a critical role in the TGF-β/ SMAD signaling pathway vital in the development and progression of cancer by regulating cellular proliferation and differentiation [42]. The TGFBR1 rs33438 polymorphism is associated with a low risk of death due to oral cancer in codominant (AG vs AA: HR=0.55, 95% CI=0.35-0.88) and dominant (GG+AG vs AA: HR=0.57, 95% CI=0.38-0.87) models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, better disease specific survival (DSS) (GG+AG vs AA: HR=0.50, 95% CI=0.29-0.85) was reported in patients given radiotherapy. There also existed a positive multiplicative interaction on DSS between the polymorphism of TGFBR1 rs334348 and radiotherapy (P=0.001) (Table 1) [42]. TGFBR1 rs334348 polymorphism may influence the progression of oral cancer by regulating the levels of TGFBR1 and inhibiting its function of phosphorylating Smad-2 and Smad-3 and consequent increased cell proliferation, a hallmark of cancer [42].…”
Section: Discussionmentioning
confidence: 99%